Interactive storytelling to nurture Islamic good values in children / Muhammad Zahin Mat Anuar - Mat Anuar, Muhammad Zahin (2014)
Learn Islamic education is required for Muslim. Islamic education act as a system of life. It include the relationship to god, human, creature and also environment. Islamic education should start while children start to thinking by itself. Current learning technique at school basically is using book and whiteboard only. There not much interactive multimedia as learning material. (Halimah, 2013). Nowadays, with the use of multimedia technology and tools in teaching is one of the most efficient ways to improve and change their current technique of learning. Islamic education game in mobile technology is one of the other technique that can be implement to help children learning with other environment and method. Each people have different learning style. Many research have been done to develop a better technique and understanding in children education. Instead of using book and whiteboard, mobile devices become efficient way for children to learn when outside the school. This research focus on designing application for children age 5-6 years old and for android market. This research is investigating a suitable technique and method to develop an application that implement multimedia technique. The research will focus implementing multimedia technique on mobile interactive storytelling that used to nurture the Islamic good values in children.